2017
DOI: 10.1111/ijpp.12353
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about medicines among Hong Kong hospital outpatients†

Abstract: Our results identified the demographic characteristics of patients with negative or hesitant belief attitudes about medicines. In order to effectively achieve improvement in long-term beliefs about medications, the design of interventions should target positively modifying belief attitudes in these two patient groups. Furthermore, addressing patients' concern about their medicines was reaffirmed to be an important criterion for researchers to focus on when designing effective interventions in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 19 publications
2
15
2
6
Order By: Relevance
“…As approximately 70% of all participants were in the high NCD group (Table ), this implies that most patients considered that their medications were necessary and less likely to be causing concern. Furthermore, participants with increasing age (from 45 to 77) and in relatively low SES tended to present a more positive attitude towards medicine as reflected by the upward trend in high NCD reporting (Tables and ), which was in line with previous studies . This was because older patients (age 62 and above, in particular) tended to consider that their conditions were more severe than others due to the increase in the prevalence of multiple chronic illnesses, the number of regularly prescribed medicines and longer duration of administering those medicines.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…As approximately 70% of all participants were in the high NCD group (Table ), this implies that most patients considered that their medications were necessary and less likely to be causing concern. Furthermore, participants with increasing age (from 45 to 77) and in relatively low SES tended to present a more positive attitude towards medicine as reflected by the upward trend in high NCD reporting (Tables and ), which was in line with previous studies . This was because older patients (age 62 and above, in particular) tended to consider that their conditions were more severe than others due to the increase in the prevalence of multiple chronic illnesses, the number of regularly prescribed medicines and longer duration of administering those medicines.…”
Section: Discussionsupporting
confidence: 86%
“…Logistic regressions demonstrated that gender and age groups (young and old‐old) were significant predictors for SRH reporting, which in turn significantly predicted their NCD response. Regular administration of the SRH item, followed by specific questioning could, in daily practice, enhances early identification of patients who may have hesitant or distrustful belief attitudes towards their medications, which may lower their intention to adhere to treatments . As such, early identification of potentially non‐adherent patients was achieved and prompt intervention or monitoring could be put in place.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations